Kenopak Lamaholot: Menemukan Makna Religius-Etis dan Didaktis Ungkapan Bijak Masyarakat Tanalein - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2021)
Kenopak, in the literary perspective can be compared with the “wisdomgenre”, found among the Lamaholot people, who live in the easternpart of Flores. Most people use the “Lamaholot” language as the spokenlanguage. Lamaholot language can be used in different ways, eitherordinary or extraordinary. Kenopak is always used in extraordinarytimes, for ritual needs or different cultural events. Using “kenopak”,the Lamaholot people try to describe the history and the role of theclan in certain social contexts, the existence of the High Being, andmany different values in different fields of life. Being conscious of theimportant values of kenopak, this study is trying to find different valuesof kenopak among the people in Tanalein, West Solor, Larantuka, andcomparing them with the values of wisdom in the Bible Tradition.Kenopak as the wisdom expression among the Lamaholot people isnot only a range of words and sentences without meaning, inheritedfrom the old generations. After doing a long research and analyzing itscontents, kenopak actually have different important values for life. Ethic,religious and didactics are the basic and fundamental values that can’tbe separated from different kenopak, that are known and acknowledgedamong the Lamaholot people. Those values have a close relation withthe basic christian values found in the Bible. Facing the changes and thedevelopment of times, those values might be useful for the formation ofyoung generations, preparing them as the generation for future.